Women Empowerment: A Literature Review - Irshad Ahmad Reshi; Dr T. Sudha (CV. Radja Publika, 2022)
Abstract Women empowerment is a critical issue in today's world, as it aims to increase women's economic, social, and political power. This literature review provides an overview of the concept of women's empowerment, its historical evolution, and its importance in achieving sustainable development goals. The review highlights the various factors that hinder women's empowerment and identifies successful strategies for empowering women, such as education, access to resources, and political participation. Finally, the review concludes with recommendations for policymakers, civil society organizations, and researchers to advance the cause of women empowerment.